The Final Destination: The Purpose of Human Life in the Perspective of the Qur'an (Thematic Interpretation Studies): Studi Tafsir Tematik - ziya, Fauziya Atsabitah (Al-Fath, 2024)
The purpose of human life has been a profound question and has dominated human thought throughout history. In the Islamic tradition, the Qur'an gives a broad view of man's ultimate goal. This article delves into the Qur'anic view of man's ultimate destination, highlighting its essence, meaning, and philosophical implications in human life. The discussion begins by explaining the concept of the afterlife, which is the culminating point of the human journey according to the Qur'an, where individuals are faced with accountability for their deeds in the world. Next, it explores the Qur'anic view of the purpose of human life, leading to the awareness of obedience to Allah, spiritual enhancement, and eternal happiness in the Hereafter. Through its teaching on the afterlife, the Qur'an provides a moral and ethical foundation for human behavior, inspiring good action and doing justice, compassion, and devotion to others. Thus, through this article, we can understand how the Qur'an provides a powerful guide on the purpose of human life, as well as how the concept of this final destination influences attitudes, values, and actions in the daily lives of Muslims.